Another Answer to the Classical Question of Historiography: Why was the Republic of the Two Nations late compared to Westem Europe? (On Darius Žiemelis’s Doctoral Dissertation ) - Čelkis, Tomas (Lietuvos istorijos studijos, 2010)
-